Peripheral Neuropathy During Concomitant Administration of Proteasome Inhibitors and Factor Xa Inhibitors: Identifying the Likelihood of Drug-Drug Interactions - Meng, Long; Huang, Jing; Qiu, Feng; Shan, Xuefeng; Chen, Lin; Sun, Shusen; Wang, Yuwei; Yang, Junqing (Frontiers in Pharmacology, 2022)
Proteasome inhibitors (PIs) cause toxic peripheral neuropathy (PN), which is one of the dose-limiting adverse events of these treatments. Recent preclinical studies find that factor Xa inhibitor (FXaI), rivaroxaban, promotes PN in animals receiving oxaliplatin. Cancer patients may receive a combined therapy of PIs and FXaIs. This study aimed to identify and characterize the interaction signals for the concomitant use of PIs and FXaIs resulting in PN. Methods US FAERS reports from the first quarter of 2004 to the first quarter of 2020 were extracted for analysis. The Standardized Medical Dictionary for Regulatory Activities (MedDRA) Query was used to identify PN cases. We conducted an initial disproportionality exploration to detect PN adverse event signals associated with the combined use of PIs and FXaIs by estimating a reporting odds ratio (ROR) with a 95% confidence interval (CI). Next, the adjusted RORs were analyzed by logistic regression analysis (adjusting for age, gender, and reporting year), and additive/multiplicative models were conducted to further confirm the findings. Additionally, subset data analysis was performed based on a single drug of PIs and FXaIs. Results A total of 159,317 adverse event reports (including 2,822 PN reports) were included. When combined with FXaIs therapy, the reported incidence of PN with PIs was associated with a significant increase (RORadj = 7.890, 95%CI, 5.321-11.698). The result remained significant based on additive/multiplicative methods. The observed association was consistent in analyses restricted to all specific PI (bortezomib and ixazomib) and FXaI (rivaroxaban) agents, except apixaban. Conclusions The analysis of FAERS data identified reporting associations of PN in the combined use of PIs and FXAIs, suggesting the necessity for further robust preclinical and clinical studies to elucidate the relationship.